Oral nitrate-reducing bacteria as potential probiotics for blood pressure homeostasis - Chai, Xiaofen; Liu, Libing; Chen, Feng (Frontiers in Cardiovascular Medicine, 2024)
Hypertension is a leading cause of morbidity and mortality worldwide and poses a major risk factor for cardiovascular diseases and chronic kidney disease. Research has shown that nitric oxide (NO) is a vasodilator that regulates vascular tension and the decrease of NO bioactivity is considered one of the potential pathogenesis of essential hypertension. The L-arginine-nitric oxide synthase (NOS) pathway is the main source of endogenous NO production. However, with aging or the onset of diseases, the function of the NOS system becomes impaired, leading to insufficient NO production. The nitrate–nitrite–NO pathway allows for the generation of biologically active NO independent of the NOS system, by utilizing endogenous or dietary inorganic nitrate and nitrite through a series of reduction cycles. The oral cavity serves as an important interface between the body and the environment, and dysbiosis or disruption of the oral microbiota has negative effects on blood pressure regulation. In this review, we explore the role of oral microbiota in maintaining blood pressure homeostasis, particularly the connection between nitrate-reducing bacteria and the bioavailability of NO in the bloodstream and blood pressure changes. This review aims to elucidate the potential mechanisms by which oral nitrate-reducing bacteria contribute to blood pressure homeostasis and to highlight the use of oral nitrate-reducing bacteria as probiotics for oral microbiota intervention to prevent hypertension.